Community Attitude Toward The Behavior Of Reducing and Handling Plastic Waste In Water Sweet Beach Area, Padang City - Hasibuan, Rira Fauziah; Syah, Nur Afrainin; Burhan, Ida Rahmah (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2021)
The aim of the study was to describe people's attitudes towards the behavior of reducing and handling plastic waste in the Air Manis Beach area of Padang City. This research method uses a qualitative approach in the form of grounded theory. The data were analyzed in two stages, namely concept formation and concept development. The results of the study describe people's attitudes towards the behavior of reducing and handling plastic waste as seen from: (1) the degree of public knowledge about plastic waste reduction and management; (2) public understanding of the impact of plastic waste; (3) cultural values believed by the community.